A transparent hybrid metal halide glassy scintillation screen for high-resolution fast neutron radiography - Zi’an Zhou; Jinxiao Zheng; Shihao Ruan; Guichu Yue; Tiao Feng; Yini An; Meimei Wu; Nü Wang; Shuyun Zhou; Linfeng He; Chenghua Sun (Nature Communications)
Abstract Fast neutron radiography offers exceptional penetration for high-density and bulky objects, yet its resolution is hindered by light scattering in conventional scintillators and screen fabrication techniques. To address this, here, we develop a transparent glassy Mn-based hybrid metal halide scintillation screen, (BTPP)1.8(HTPP)0.2MnBr4 (BTPP+ = butyltriphenylphosphonium, HTPP+ = heptyltriphenylphosphonium), leveraging temperature-dependent ordered-disordered transitions. The large-area screen boasts >70% visible light transmittance (500–800 nm), a high photoluminescence quantum yield (~85.54%), and threefold higher light output than commercial ZnS (Ag): PP screens. With a spatial resolution of 5 lp mm−1, it surpasses existing scintillators. This hybrid material enables imaging of heavy objects with clear hierarchical details, providing accurate data for non-destructive detection while offering an alternative approach to scintillator design, advancing the potential of fast neutron radiography.